Stealing Deposits: Deposit Insurance, Risk‐Taking, and the Removal of Market Discipline in Early 20th‐Century Banks - CALOMIRIS, CHARLES W.; JAREMSKI, MATTHEW (Journal of Finance, 2019)
ABSTRACT Deposit insurance reduces liquidity risk but can increase insolvency risk by encouraging reckless behavior. Several U.S. states installed deposit insurance laws before the creation of the Federal Deposit Insurance Corporation, and those laws applied only to some depository institutions within those states. These experiments present a unique testing ground for investigating the effect of deposit insurance. We show that deposit insurance removed market discipline constraining uninsured banks. Taking advantage of World War I's rise in world agricultural prices, insured banks increased their insolvency risk and competed aggressively for deposits. When prices fell after the war, the insurance systems collapsed and suffered high losses.